Penerapan Teknologi Automatic Level Crossing Di Indonesia - Imron, Nanda Ahda; Rachman, Natriya Faisal; Wirawan, Willy Artha; Aghastya, Adya (Politeknik Perkeretaapian Indonesia Madiun, 2018)
Indonesia has many Level Crossing (LC) all of which are still manual with poor performance. As a result, accidents often occur. This accident was caused by the guards who late lowered the doorstop, carelessness and impatience of road users. Erratic waiting times on LC cause delays and high queues and trigger road users to break through LC doors. In Jakarta, the LC manual causes significant disruption to road users; the delay is 158.46 seconds and the queue is 66.85 m as is the case in Malang, Pasuruan and Surakarta. Many countries have implemented Automatic Level Crossing (ALC) successfully, such as the United Kingdom, Japan and Australia. ALC not only reduces disruption to road users but also minimizes human error (especially for LC manual guards). The most suitable type of ALC for Indonesia is Crossing Barrier with Obstacle Detection (CBOD). This study proves that CBOD is able to reduce disruption to road users to delay to 125,393 seconds and queue to 60,778 m. On the other hand, to control the behavior of road users needs to be supported by the installation of traffic calming; noise band, traffic channel and countdown timer. Analysis of B / C Ratio in CBOD installations including traffic calming produces tilapia 1.24, which is feasible to apply.